Low-calcination temperature to synthesize a-alumina from aluminium waste can using sol-gel method - Omer, A. H.; Mokaizh, A. A.; Jun Haslinda, Shariffuddin (IOP Publishing Ltd, 2021)
Many countries around the world are facing issues in managing solid waste materials; most of these wastes such as aluminium can are deposited to the landfills, leading to environmental pollution. Recycling is considered as an effective technique to manage the aluminium can waste since it can provide benefits in terms of energy savings, reduce volumes of waste and cost-effectiveness. In this article, it was desired to turn the aluminium can waste into α-Alumina using sol-gel method. Alumina exists in many crystalline structures which degenerate to the most stable hexagonal α-phase at high temperatures. α-Alumina (a-Al2O3) is the most stable crystalline structure widely used and studied as electronic packaging, corrosion resistance ceramics, high-temperature structural material, and translucent ceramics. FTIR, XRD, SEM-EDX, TGA, and BET were employed to investigate the properties of a-alumina. The experimental results obtained from this study demonstrates the possibility of producing alumina from an aluminium can waste with the exact surface area of 5.2105 m2/g, crystallite size at 132.50 nm and total weight loss of 2.71% at 900 C calcination temperature.